Effect of epigallocatechin gallate on dental biofilm of Streptococcus mutans: An in vitro study - Mor Schneider-Rayman; Doron Steinberg; Ronit Vogt Sionov; Michael Friedman; Miriam Shalish (BMC, 2021)
Abstract Background Streptococcus mutans (S. mutans) plays a major role in the formation of dental caries. The aim of this study was to examine the effect of the green tea polyphenol, epigallocatechin gallate (EGCG), on biofilm formation of S. mutans. Methods Following exposure to increasing concentrations of EGCG, the planktonic growth was measured by optical density and the biofilm biomass was quantified by crystal violet staining. Exopolysaccharides (EPS) production was visualized by confocal scanning laser microscopy, and the bacterial DNA content was determined by quantitative polymerase chain reaction (qPCR). Gene expression of selected genes was analyzed by real time (RT)-qPCR and membrane potential was examined by flow cytometry. Results We observed that EGCG inhibited in a dose-dependent manner both the planktonic growth and the biofilm formation of S. mutans. Significant reduction of S. mutans biofilm formation, DNA content, and EPS production was observed at 2.2-4.4 mg/ml EGCG. EGCG reduced the expression of gtfB, gtfC and ftf genes involved in EPS production, and the nox and sodA genes involved in the protection against oxidative stress. Moreover, EGCG caused an immediate change in membrane potential. Conclusions EGCG, a natural polyphenol, has a significant inhibitory effect on S. mutans dental biofilm formation and EPS production, and thus might be a potential drug in preventing dental caries.